Making Women's Voices Count in Natural Disaster Programs in East Asia and the Pacific - Trohanis, Zoe Elena; Svetlosakova, Zuzana; Carlsson-Rex, Helene (World Bank, Washington, DC, 2012)
The East Asia region is highly prone to the impacts of natural disasters. Situated in the ring of fire, countries in the region are regularly hit by typhoons, earthquakes, floods, and other events. Natural disasters can have major impacts on the social and economic welfare of a population, and often pose serious obstacles in the achievement of sustainable social and economic development. Moreover, impacts from disasters are not uniformly distributed within a population and tend to disproportionately affect the poorest and most marginalized groups. Women are at a particular risk. Women often experience higher rates of mortality, morbidity and post-disaster diminishment in their livelihoods. Several underlying factors exacerbate women's vulnerability to the impacts of disasters, such as lack of means to recoup lost assets, limited livelihood options, restricted access to education and basic services, and in many cases, also socio-cultural norms. This note explores some of the underlying issues that are linked to gender and vulnerability to natural disasters and offers examples of how to address some of these issues in disaster risk management programs.